???? ????? ?????? ?? ??????? ?? ???? ??????? ???????? - Anisa Listiana (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2016)
Translation is a communication activity to understand the existence of another nation with the peculiarities of the language. Arabic is language through which the revelation of Qur'an was revealed. For Arabic, at the initial appearance, science and sharf nahwu intended only as a means of learning to anticipate the spread of language errors. But in its development, nahwu and sharf is a independent discipline that is heavily influenced by Greek philosophy that science is complex and convoluted. This complexity demands for anyone whose background non-Arabs for more in depth to be able to translate and understand the main revelation is revealed through the Arabic language. Arabic and Indonesian are the two languages that were born from two different language families. Of these two languages have similarities and differences. Different characteristics (sui generis) within each language requires precise translation process. Indeed, sometimes there is stiffness in translation. In this context, knowledge of grammar / classification grammatical study of morphemes, words, phrases, sentences so as to form a discourse, other Dalan is very important and the massive benefits in translation. Grammar and other knowledge is a discussion within the discipline nahwu and sharf as a separate science disciplines.